HOXC8 regulates self-renewal, differentiation and transformation of breast cancer stem cells - Shah, Mansi; Cardenas, Ryan; Wang, Belinda; Persson, Jenny; Mongan, Nigel P.; Grabowska, Anna M.; Allegrucci, Cinzia (BioMed Central, 2017)
Background: Homeobox genes are master regulators of cell fate during embryonic development and their expression is altered in cancer. By regulating the balance between cell proliferation and differentiation, they maintain homeostasis of normal tissues. Here, we screened the expression of homeobox genes in mammary stem cells to establish their role in stem cells transformation in breast cancer. Methods: Using a Homeobox Genes PCR array, we screened 83 homeobox genes in normal cancer breast stem/progenitor cells isolated by flow cytometry. The candidate gene HOXC8 epigenetic regulation was studied by DNA methylation and miRNA expression analyses. Self-renewal and differentiation of HOXC8-overexpressing or knockdown cells were assessed by flow cytometry and mammosphere, 3D matrigel and soft agar assays. Clinical relevance of in vitro findings were validated by bioinformatics analysis of patient datasets from TCGA and METABRIC studies. Results: In this study we demonstrate altered expression of homeobox genes in breast cancer stem/progenitor cells. HOXC8 was consistently downregulated in stem/progenitor cells of all breast molecular subtypes, thus representing an interesting tumour suppressor candidate. We show that downregulated expression of HOXC8 is associated with DNA methylation at the gene promoter and expression of miR196 family members. Functional studies demonstrated that HOXC8 gain of function induces a decrease in the CD44+/CD24-/low cancer stem cell population and proportion of chemoresistant cells, with a concomitant increase in CD24+ differentiated cells. Increased HOXC8 levels also decrease the ability of cancer cells to form mammospheres and to grow in anchorage-independent conditions. Furthermore, loss of HOXC8 in non-tumorigenic mammary epithelial cells expands the cancer stem/progenitor cells pool, increases stem cell self-renewal, prevents differentiation induced by retinoic acid and induces a transformed phenotype. Conclusions: Taken together, our study points to an important role of homeobox genes in breast cancer stem/progenitor cell function and establishes HOXC8 as a suppressor of stemness and transformation in the mammary gland lineage